Biochar Alteration of the Sorption of Substrates and Products in Soil Enzyme Assays - Mark Swaine; Rachel Obrike; Joanna M. Clark; Liz J. Shaw (Applied and Environmental Soil Science)
Pine wood and barley straw biochar amendments to Kettering and Cameroon sandy silt loam soils (15, 30, or 150 mg biochar g−1 soil) caused significant reductions (up to 80%, P<0.05) in concentrations of substrate and extractable product in soil dehydrogenase and phosphomonoesterase enzyme assays. Likely this was caused by increased solid-phase sorption of the chemicals in the presence of the biochars under assay conditions. The relationship between assay chemical sorption and biochar concentration depended on the chemical, soil type, biochar type, and their interactions; hence, no uniform correction factor could be derived. This biochar impact on assay constituents will limit the identification of genuine biochar effects on soil enzymes. It is recommended that the assumption of saturating substrate concentrations be checked and that product standards be matrix-matched when conducting enzyme assays with biochar-amended soil.